Draft Annual Plan 1971-72-Maharashtra - Planning Commission (Planning Commission, 1971)
The emphasis in the recent years has been mainly on the use of hybrid and high yielding varieties of seeds. The area under the hybrid and high yielding varieties programme has increased from 10.07 lakh hectares in 1968-69 to 14.94 lakh hectares in 1970-71. The increase has been marked mainly in areas under paddy wheat and Bajra while the increase in the area under the high yielding Jowar has been marginal.
Government of Maharashtra Planning Commission (Programme Administration Division)